Synergy Realization in Post-Acquisition Integration : Role of Strategic Alignment - Marttila, Heidi (My University, 2026)
Synergy realization is an important strategic process for companies engaged in mergers and acquisitions. Its intended impact is to ensure that the strategic rationale of the acquisition translates into coherent decision-making, coordinated integration actions, and aligned ways of working across the combined organization. To ensure this, strategic alignment between merging companies forms the foundation for effective integration, the realization of operational synergies, and improved post-acquisition performance with value creation. The development of strategic alignment and the design of integration strategy are closely interconnected processes. Clear alignment at the strategic level guides integration priorities, defines synergy targets, and shapes the degree and pace of integration. In this way, strategic alignment and integration execution are mutually reinforcing elements that together determine whether the acquisition’s intended value creation can be successfully achieved. This thesis examines how strategic alignment drives the realization of operational synergies in companies by exploring the connection between strategic alignment and post-acquisition integration outcomes. A qualitative case study approach was conducted involving four Finnish multinational companies that have acted as either acquirers or targets in M&A transactions and have recent experience in post-acquisition integration processes. The research combines a comprehensive literature review on strategic alignment, synergies, and integration strategies with empirical data from the companies, and their case acquisitions, including semi-structured interviews with key integration stakeholders and further analysis of integration. This approach enables an in-depth understanding of how strategic alignment shapes integration strategy and facilitates synergy realization during the post-acquisition phase. The study finds that companies should prioritize the role of strategic alignment when acquisition rationale creates a need to secure effective synergy realization. In the case acquisitions studied, differences in strategic intent, operating models, and market positioning acted as catalysts for emphasizing alignment during the post-acquisition integration phase. Strong strategic alignment clarified integration priorities, aligned expectations regarding achievable synergies, and provided a direction for decision-making across the combined entity. The findings indicate that a selective and well-timed integration approach enhanced synergy realization by focusing on operational areas where value could be captured with minimal disruption. Rather than pursuing full-scale integration immediately, successful firms adopted a phased approach that preserved existing capabilities while gradually expanding integration efforts. This approach strengthened commitment, reduced organizational resistance, and improved transparency in synergy tracking. Strategic alignment created a link between the original acquisition rationale and day-to-day operational execution. By aligning integration strategies with clearly defined strategic objectives, firms were better able to translate long-term value creation goals into concrete operational synergies. In this way, strategic alignment not only facilitated immediate synergy realization but also reinforced the strategic coherence and competitive positioning of the combined organization over time. This thesis contributes to the international business and M&A literature by bridging the relationship between strategic alignment and operational synergy realization in post-acquisition integration. Strategic alignment is positioned as a mechanism that connects acquisition rationale with effective execution, thereby playing an integral role in transforming synergies into value and sustained competitive advantage. The findings offer practical guidance for managers on how to design integration efforts in a way that strengthens strategic coherence and accelerates synergy realization.

Synergioiden toteuttaminen on tärkeä strateginen prosessi yrityksille, jotka osallistuvat yritysostoihin. Sen tavoitteena on varmistaa, että yritysoston strateginen perustelu konkretisoituu johdonmukaisena päätöksentekona, koordinoituina toimenpiteinä ja yhtenäisinä toimintatapoina yhdistetyssä organisaatiossa. Tämän varmistamiseksi sulautuvien yritysten välinen strateginen yhdenmukaisuus muodostaa perustan integraatiolle, operatiivisten synergioiden realisoitumiselle sekä yritysoston jälkeisen suorituskyvyn ja arvonluonnin parantumiselle. Strategisen yhdenmukaisuuden kehittäminen ja integraatiostrategian suunnittelu ovat toisiinsa kytkeytyviä prosesseja. Selkeä strateginen linjaus ohjaa integraation painopisteitä, määrittää synergiatavoitteet sekä muovaa integraation laajuutta ja etenemisvauhtia. Näin strateginen yhdenmukaisuus ja integraation toteutus vahvistavat toisiaan ja yhdessä ratkaisevat, voidaanko yritysoston tavoiteltu arvonluonti saavuttaa onnistuneesti. Tämä tutkielma tarkastelee, miten strateginen yhdenmukaisuus ohjaa operatiivisten synergioiden toteutumista, selvittämällä strategisen yhdenmukaisuuden ja integraatiotulosten välistä yhteyttä. Tutkimus toteutettiin laadullisena tapaustutkimuksena, johon osallistui neljä suomalaista monikansallista yritystä, jotka ovat toimineet joko ostajina tai kohdeyrityksinä yrityskaupoissa. Tutkimuksessa yhdistetään kattava kirjallisuuskatsaus strategiseen yhdenmukaisuuteen, synergioihin ja integraatiostrategioihin sekä tarkastelluista yritysostoista kerätty empiirinen aineisto, mukaan lukien puolistrukturoidut haastattelut keskeisiltä toimijoilta sekä integraatiovaiheen analyysi. Tämä lähestymistapa mahdollistaa syvällisen ymmärryksen siitä, miten strateginen yhdenmukaisuus muovaa integraatiostrategiaa ja edistää synergioiden toteutumista yritysoston jälkeisessä vaiheessa. Tutkimus osoittaa, että yritysten tulisi painottaa strategisen yhdenmukaisuuden merkitystä silloin, kun yritysoston perustelut luovat tarpeen varmistaa synergioiden tehokkaan toteutumisen. Tarkastelluissa yritysostoissa erot strategisissa tavoitteissa, toimintamalleissa ja markkina-asemoinnissa toimivat katalysaattoreina strategisen yhdenmukaisuuden korostamiselle integraatiovaiheessa. Vahva strateginen yhdenmukaisuus selkeytti prioriteetteja, yhdenmukaisti odotuksia saavutettavista synergioista ja tarjosi suuntaa päätöksenteolle. Tulokset viittaavat siihen, että valikoiva ja oikea-aikainen integraatiolähestymistapa edisti synergioiden toteutumista keskittymällä niihin operatiivisiin osa-alueisiin, joilla arvoa voitiin saavuttaa vähäisin häiriöin. Sen sijaan, että olisi pyritty välittömästi täysimittaiseen integraatioon, menestyneet yritykset omaksuivat vaiheittaisen lähestymistavan, joka säilytti olemassa olevat kyvykkyydet ja laajensi integraatiotoimia asteittain. Tämä vahvisti sitoutumista, ja paransi synergioiden seurannan läpinäkyvyyttä. Strateginen yhdenmukaisuus loi yhteyden alkuperäisen yritysostoperustelun ja päivittäisen operatiivisen toteutuksen välille. Yritykset kykenivät paremmin muuntamaan pitkän aikavälin arvonluontitavoitteet konkreettisiksi operatiivisiksi synergioiksi yhdenmukaistamalla integraatiostrategiat selkeästi määriteltyihin tavoitteisiin. Näin strateginen yhdenmukaisuus ei ainoastaan edistänyt välitöntä synergioiden toteutumista, vaan myös vahvisti yhdistetyn organisaation strategista johdonmukaisuutta ja kilpailuasemaa pitkällä aikavälillä. Tutkimus täydentää kansainvälisen liiketoiminnan ja yritysjärjestelyjen tutkimuskirjallisuutta yhdistämällä strategisen yhdenmukaisuuden ja operatiivisten synergioiden toteutumisen näkökulmat. Tulokset tarjoavat käytännön ohjeita johtajille siitä, miten integraatiotoimet voidaan suunnitella tavalla, joka vahvistaa strategista yhdenmukaisuutta ja nopeuttaa synergioiden toteutumista.
Keywords: Mergers and Acquisitions; Synergy Realization; Strategic Alignment; Integration; Strategy